Ligan baru yang selektif terhadap Cu(II) dalam transport membran cair = A New Carrier Exhibiting Cu (II) Selective Across Liquid Membrane Transport - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Poly(eugenyl oxyacetic) acids had been synthesized and its utilization as a novel carrier for metal ions transport through a liquid membrane had been investigated. The monomer eugenyl oxyacetic was prepared by Williamson synthesis of eugenol and cloroacetic acid in aqueous media. Poly(eugenyl oxyacetic) acid had been obtained by cationic polymerized of eugenyl oxyacetic using of concentrated sulphuric acid as the catalyst. The chemical structure of monomer was confirmed by IR, MS ang 1H NMR spectrometry while for the chemical structure of polymer was confirmed by IR and 1H NMR and viscometry was used for determination of average molecular weight. Cationic transport studies had been carried out in a U-tube type glass cell where chloroform solution of the polymer as the liquid membrane was placed in the bottom of the cell separating source phase and receiving phase in the other side of the tube. All the phase were stirred at c.a 300 rpm during exsperiment. The source phase were 0.01 M aqueous solution of Na, K, Ca, Mg, Fe(III), Ni(II), Co(II), Cu(II) and Zn(II) at pH=6.2 by accetate buffer solution while that for receiving phase 0.1 M HC1. During the course experiment, both phases were sampled for determination of the metal ion concentration by atomic absorption spectrometry. The result showed that poly(eugenyl oxyacetic) acid was an excellent carrier for selective transport of Cu(II). The efficiency of the "uphill" transport for Cu(II) achieved 94.93% after 24 h. Under the same condition, the transport efficiencies for Zn(II), Ca(II) and Ni(II) were 65.59, 39.66 and 10.87%, respectively, while those for other cations under examinations were less than 10%.